Design and simulation of periodic dielectric waveguide-based optical switch - Chia, Zong Hong. (2010)
Optical switches are components in a fiber-optic communications network that direct light beams from one optical fiber to another. In the course of my project, only optical switches that manipulate light beams directly are studied. The purpose of the project is to design and simulate periodic dielectric waveguide optical switches that allows light to pass through at certain frequencies and prevents transmission at other frequencies. The fundamental theories of light propagation were explored and the operating principles of the optical switches were researched to apply as much knowledge from this information into the project itself. In this project, the periodic rectangular strip and periodic air-hole waveguides are designed and simulated to achieve high transmission at the output while in the “On” mode and minimum transmission while in the “Off” mode. Various parameters like the width, length and air-gap of the devices are tuned to minimize losses in the waveguide to achieve the desired output. Familiarization of the Rsoft software is required throughout this whole project such as to set the parameters and dimensions correctly to as to achieve results as accurately as possible. After the simulations, the simulation results were analyzed and the optimum results are acquired from this process. Finally, the two periodic dielectric waveguide based optical switches were completed with a relatively good output at both the “On” and “Off” modes.